Maternal attachment levels of advanced age mothers and relation factors - Eylem Toker; Mehtap Omac Sonmez; Cemile Ozyesıldag; Gamze Akbulut (Acta Scientiarum. Health Sciences, 2024)
Being mother at advanced age is associated with physical, emotional and social problems during pregnancy. The purpose of study to finding out the maternal attachment of pregnant women of advanced age and the associated factors. The methodology used was a descriptive and cross-sectional research. The minimum sample size was calculated as 323 in a confidence interval of 95%, with a margin of error of 5%. Total 278 pregnant women were included in this study. Data were collected through Personel Information Form and the Maternal Attachment Inventory. Non-parametric tests (Kruskal-Wallis,Mann-Whitney U), logistic regression analysis was performed for evaluating statistically significant data.  The mean of Maternal Attachment Inventory scores is 97.22 ± 17.38 points. The maternal attachment level was higher in cases in which the mother did not work (O.R:0.944), the epidural anesthesia was used (O.R:2.937), the mother had low number of stillbirths (O.R:0.868), the mother gave birth to male infant (O.R:1.022), the newborn had high birth weight (O.R:1.038), the newborn had congenital anomaly (O.R: 0.795) and the mother had no skin-to-skin contact (O.R:0.933). we conclude that though it was discerned that mothers of advanced age had high levels of MA, it was identified that the MA level was affected by certain demographic variables.